VD_FINDINFO Jug / 2015 / 14 vom 9. Juli 2014 - VD Tribunal cantonal (2014)
LOI FÉDÉRALE SUR LES ÉTRANGERS, SÉJOUR ILLÉGAL, ACTIVITÉ LUCRATIVE, PEINE, CHOIXEN GÉNÉRAL, PEINE PÉCUNIAIRE | 34 CP, 41 CP, 47 CP, 115 LEtr